2000
DOI: 10.1007/s007010050030
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent in Neurosurgery: Patients' Recall of Preoperative Discussion

Abstract: The general principles of memory apply and have implications in states of emotional arousal. Whereas education and age, unlike in previous reports, did not appear to influence recall, thus indicating that we had succeeded in tailoring IC to the individual, recall rate was low in most cases. Physicians should highlight the discrepancy and conflict between the requirements for the defence of medical practice in the law courts and the actual interests of patients. They should promote research to establish what re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 14 publications
3
65
1
3
Order By: Relevance
“…However, in the current study, recall was significantly better for paralysis (P = 0.047) and recurrence (P = 0.019) if the consent-to-surgery period was greater than 2 weeks. Unlike prior studies [11], we found that younger patients had greater recall for risks of the operation, significantly so for infection risk.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in the current study, recall was significantly better for paralysis (P = 0.047) and recurrence (P = 0.019) if the consent-to-surgery period was greater than 2 weeks. Unlike prior studies [11], we found that younger patients had greater recall for risks of the operation, significantly so for infection risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Krupp et al [11] found that on average, patients remembered 18% of information 2 h after consenting for neurosurgical operations, with a mean recall of 4 risks out of 25 disclosed for spinal operations. However, in the current study, recall was significantly better for paralysis (P = 0.047) and recurrence (P = 0.019) if the consent-to-surgery period was greater than 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most of the patients remembered less than half of the items that were presented as major risks associated with cesarean delivery. Previous studies in other specialties have described similar findings concerning the poor ability of patients to recall the details of the consent interview [7][8][9][10][11][12]. Several factors are thought to be responsible for this.…”
Section: Discussionsupporting
confidence: 67%
“…Potentially, a patient's level of understanding and recall of what was discussed during the consent process for cesarean delivery reflects the quality of the process. Attempts have been made to evaluate the quality of the consent process in other specialties, including general surgery, orthopedics, dermatology, neurology, otolaryngology, and anesthesia [6][7][8][9][10][11][12]. However, data are limited regarding the evaluation of the consent process in obstetrics.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, several studies have found that patient comprehension and recall of information is limited [16,17]. Three examples from surgery illustrate these limitations: On average, only 2 out of 5 complications were recalled in the context of elective plastic surgery [18]; 5 out of 32 pieces of information were correctly remembered 2 h after the preoperative discussion prior to brain surgery and 4 out of 25 pieces of information prior to spinal surgery [19] (for a recent review, see [20]). Questionnaire data from patients with advanced metastatic cancer revealed how little patients understood of their clinical situation.…”
Section: Introductionmentioning
confidence: 99%